Migration and Identity through Creative Writing StOries: Strangers to Ourselves - Kumar, Alka; Triandafyllidou, Anna (IMISCOE Research Series,, 2024)
This open access book brings together storytelling and self-narrative, creative writing and narrative enquiry to explore a variety of topics in migration from an experiential lens. The volume is hybrid and multi-genre as it contains both scholarly chapters grounded in academic perspectives, as well as personal essays and creative non-fiction. In addition to critical reflections on key migration topics and concepts - like, identity and diversity, integration and agency, transnationalism and return - the scholarly chapters also propose a particular methodology for 'workshopping' migration narratives, and writing about (personal) lived experiences through iterations of scientific reflection, narrative enquiry, and creative imagination. The book explores the potential of a new conceptual paradigm and methodological process to learn more, and also `differently,' about the migration experience. Finally, this volume asks a bigger question too - how do we define the boundaries of research; isit possible to entirely separate the spatial, temporal and methodological parameters in which projects are developed and pursued; and how can the specifics of these multiple contexts contribute to shaping the knowledge being produced?